Measuring match quality using subjective data - Ferreira, Priscila (2010)
We examine whether data routinely collected in household surveys and surveys of workers can be used to construct a measure of underlying match quality between worker and firm which helps test matching models and predict subsequent labour market outcomes of workers. We use subjective data from employees both on reported levels of job satisfaction with various aspects of the current job and on whether they would like a new job with a new employer to construct a measure of underlying match quality. We then use this to test several implications of matching models relating to wage-tenure profiles, wages, and separations.